Mandibular Condylar Cartilage Growth: Literature Review - Berrios Mamula, Karla (2022)
The mandibular condylar cartilage is a specialized structure present on the surface of the mandibular condyles. This review of the literature will allow you to get current information about the structure of the mandibular condylar cartilage, the factors that influence the growth of this and review the current studies on the morphological changes that may occur in the cartilage with aging. A systematic review of recent scientific articles was carried out. The results obtained in the Indian review show that the structure of the mandibular condylar cartilage presents four layers, also, the hyaline cartilage that conforms to it, presents mature and hypertrophic chondroblasts even in advanced ages. It offers the possibility that it can be manipulated without considering the age as a limit factor. Studies carried out in Indian animals that the mandibular condylar cartilage can be influenced by factors such as: diet, age, sex, psychological stress, intrinsic factors, application of botulinum toxin and laser. These results establish the basis for future studies for the purpose of implementing potential treatments that can help patients with degenerative processes in the ATM, such as osteoarthritis. In the same way, it is important to promote the realization of new studies focused on the application of botulinum toxin and laser, for functional orthopedic therapies to early ages, to reduce the surgical treatments, to improve the quality and effectiveness of the currently known treatments.